Finite element study of 3D printed lattice structures with geometric imperfections - Chiu, Dowen Wei Han (Nanyang Technological University, 2021)
This report presents the investigation on the finite element study of 3D-printed lattice structure with geometric imperfections. Finite element analysis software, ABAQUS, was used exclusively for the project to perform non-linear structural analysis of the model lattice structure. The lattice structure was constructed with the Body-centred Cubic (BCC) unit cell to create a 4x4x5 model, with 1D beam element being used to model the lattice. The report is divided into two main portions, with the first part performing 20% compression analysis on the lattice structure to investigate the elastic region and plastic deformation of the lattice structure. Various attempts were made to improve stiffness of the lattice structure via manipulation of the boundary condition imposed on the lattice structure to simulate the experimental results as closely as possible. In the latter phase of the report, investigation is carried out on the response of the lattice structure with the addition of strut imperfections that may arises in the structure, that occurs inherently due to the nature of the 3D printing process. The struts imperfections were simulated via reduced diameter of the struts as well as geometric imperfection via additional joints in the BCC unit cells. The investigation of the imperfections serves to allow the incorporation of the defects, from the printing process, into the strut elements of the lattice structure to better understand the effects of imperfections and ultimately improve the predictive capabilities for simulation models for future projects. Lastly, the report summarises the results and observations made during the study and outlines future developments that may be explored subsequently after the project.